Estimation of Stature from Craniofacial Dimensions (Bangladesh Journal of Anatomy, 2014)
Context: Anthropometric studies provide a quantitative description of different parts of human body and these studies in different populations have also stated the proportional correlations among different measurements. Stature is one of the most important parameters in the identification of an individual living or dead. Identification of an individual from fragmented remains is still a very challenging task for forensic experts in spite of many studies carried out across the globe including Bangladesh because regression equations or multiplication factors formulated in a particular population group do not fit elsewhere. Several studies have shown that values of stature and craniofacial dimensions are race, ethnicity, age, gender, diet and climate sensitive. Stature can be estimated from head circumference and bigonial breadth by using linear regression equations and multiplication factor.Materials and Method: This is a cross sectional, analytical type of study conducted in the Anatomy Department of Sir Salimullah Medical College, Dhaka, from January 2010 to June 2011. One hundred Bangladeshi 25 to 45 years old women were selected for the study. Fourth class female employees of Sir Salimullah Medical College and Mitford Hospital and part time housemaids of Mitford area were selected by purposive sampling as study subjects.Results: The mean values of stature, head circumference and bigonial breadth were 148.46 ± 5.6901 cm, 53.27 ± 1.3151 cm and 9.18 ± 0.6528 cm respectively. Multiplication factor for measuring stature from head circumference and bigonial breadth were 2.79 ± 0.1056 (Mean ± SD) and 16.26 ± 1.2629 (Mean ± SD). Regression equations were calculated for estimating stature(S) from head circumference(HC) and bigonial breadth(BB) which are S=71.416 + 1.448(HC) and S=144.656 + 0.418(BB). No significant difference was found between the measured and estimated stature by using ‘t’ test. Regression equation calculated for measuring stature from head circumference showed high degree of reliability and accuracy.Conclusion: The result indicates the effectiveness of measuring stature from head circumference and bigonial breadth by using linear regression equation and multiplication factor.Bangladesh J. Anat. 2014; 12(2) : 56-61